Functional interaction between orexin/dynorphin transmission in the posterior paraventricular nucleus of the thalamus following alcohol dependence: mediation of alcohol-seeking behavior - Flores-Ramirez, Francisco J.; Pascasio, Glenn; Martin-Fardon, Rémi (Frontiers in Pharmacology, 2025)
Stress is a major contributor to the chronic nature of alcohol use disorder (AUD). Orexin (OX) neurons project to the paraventricular nucleus of the thalamus (PVT)—particularly the posterior part (pPVT)— a structure that plays a key role in stress regulation. The blockade of OX receptors in the pPVT was shown to prevent the stress-induced reinstatement of alcohol seeking in alcohol-dependent rats. Accumulating evidence indicates interactions among OX and dynorphin (DYN) in the pPVT, but unclear is the role of OX and DYN transmission in the pPVT in the stress-induced alcohol seeking during alcohol abstinence. Male Wistar rats were trained to self-administer 10% alcohol for 3 weeks. They then underwent 6 weeks of chronic intermittent alcohol vapor exposure to induce dependence. After 12 extinction sessions (∼3 weeks of abstinence), the rats received intra-pPVT infusions of the dual OX receptor antagonist TCS1102 (15 µg/0.5 µL), the κ-opioid receptor (KOP) antagonist nor-binaltorphimine (norBNI; 4 µg/0.5 µL), or their combination, and they were assessed for their reactivity to the stress (footshock)-induced reinstatement of alcohol-seeking behavior. In dependent rats, TCS1102 and norBNI reduced reinstatement but, when co-administered, their individual effects were modulated. At the time of testing, increases in Hcrt and Pdyn mRNA expression in the hypothalamus and a decrease in Hcrtr1 expression and an increase in Oprk1 expression in the pPVT were observed. These findings reveal a functional interaction among OX receptor and KOP signaling in the pPVT that underlies relapse that is precipitated by stress post-dependence, underscoring the value of multi-target interventions to restore pPVT function and prevent relapse.